Comparative analysis of the quantity and quality of both synthetic and biodegradable films on kitchen waste. (2022) - Datta, Deepshikha; Shetty, Aditya; Das, Bimal
Abstract: The huge demand for plastic use, inadequacy in waste management, and casual community behavior towards proper disposal creates a remarkable threat to life on Earth. The garbage waste, which consists of plastic bags upon exposure to rainwater and the moisture content present in the landfill, proceeds to leachate generation. This poses a major influence on the design and operation of the landfill. The present work emphasizes the effect of different types of polymeric films on kitchen waste, which is a major portion of municipal solid waste. The study has been conducted considering different polymeric films, including LDPE, starch, and LDPE blended starch film of different wt% (4 wt%, 8 wt% & 12 wt%). The objective of the present work is the keen observation of the bed height settlement of kitchen waste having different weight percent of polymeric films and the measurement of the leachate volume taken out from different containers before and after centrifugation. The quality and property of leachate have been checked by considering various parameters like COD, pH, conductivity, and salinity. It has been noticed that there is an encouraging effect on prolonged biodegradation on leachate formation and successive waste bed settlement due to the presence of plastics. It was observed that 4 wt% of LDPE blended starch film has an optimal effect on waste disposal. Hence the present work will assist in mollifying the alarming threat inflicted by plastic disposal on municipal organic solid waste.